Ṭarīqatu Ta’līm Mahāratul Kalām Li Ṭalibāt Al-Mustawā Al-Wusṭā Al-Muassasah ‘Alā ‘Ilm An-Nafsī At-Taṭawwurī - yana elita ardiani (University of Darussalam Gontor, 2018)
AbstractThe method of teaching is the important factor for the success of learning the skill of speech within and outside the classroom. Without the appropriate method of psychological status of students, teaching the skill of speech will not go on full swing. Some research points out that psychological factors are the most important factor in the success of Arabic language education because psychological factors are the intrinsic factors in the same students that encourage them and encourage them to continue to learn and develop their language abilities. This method is based on the patterns of education of the young. It means that the entrance to education and the basic assumption of the education of young people is that young students differ in adult students psychologically, experimentally and mentally. Learning in childhood includes teaching arts with principles, methods, strategies and techniques. It is said to be an art because it requires the important factors of interest towards different students, their interest in the way they are taught, and so on. The method of teaching the skill of speech used must be appropriate to the psychological conditions of the students, meaning that the method must follow the suitability of students and students, not the students who have to follow and adapt the method.Keywords: The method of teaching, Speech skills, Middle level, Students, Evolutionary psychology. طريقة تعليم مهارة الكلام لطالبات المستوى المتوسط المؤسسة على علم النفس التطوري.يانا إيليتا أرديانيجامعة دار السلام كونتورملخصطريقة التعليم هي العوامل المهمة لنجاح تعلم مهارة الكلام داخل الفصل وخارجه. فبدون الطريقة المناسبة بحالة نفسية الطالبات، فتعليم مهارة الكلام لن يسير على قدم وساق. ويشير بعض الأبحاث أن العوامل النفسية هي العامل الأبرز في نجاح تعليم اللغة العربية، وذلك بسبب العوامل النفسية هي العوامل الجوهرية (الداخلية) الواردة في نفس الطالبات التي تشجعهن وتحفزهن على الاستمرار في تعلم وتطوير قدراتهن اللغوية. أن هذه الطريقة تبنى على أنماط تعليم الصغير. معناه أن مدخل التعليم والافتراض الأساسي من تعليم الصغار هو أن طالبات الصغار تختلف بطالبات الكبار نفسيا وتجربة وعقلية. وأما التعلم في مرحلة الطفولة تشمل فنون التدريس بالمبادئ، والطريقة، والاستراتجيات، والتقنيات. ويقال أنه فن لأن فيه الحاجة بالعوامل المهمة في اهتمام نحو الطالبات المختلفة صفتها، واهتمام نحو طريقة التعليم المطابقة عنده، وغير ذلك. فطريقة تعليم مهارة الكلام المستخدمة لا بد أن تكون مناسبة لأحوال النفسية لدى الطالبات، معناه أن الطريقة يجب أن تتبع وتناسب وتلائق الطالبات وليس الطالبات التي تضطرن لمتابعة وتكيف الطريقة.الكلمات الرئيسة: طريقة تعليم مهارة الكلام، طالبات المستوى المتوسط، علم النفس التطوري